Non sustainable development. Oceans - changes and consequences. - Lubomír NÁTR (Kvasny Prumysl, 2006)
Oceans cover some 3 quarters of the Earth's surface and play an important role in water and mineral element cycling as well as in the global climate change. The main consequences of the recent temperature increase include sea level rise due to both glacier melting and volume expansion. The role of oceans in absorbing considerable part of the CO2 from the atmosphere is also important. Huge amounts of methane hydrates recently found on the seabed could contribute to the energy supply but also to an abrupt atmospheric increase in the concentration of the green house gases. Paradoxically, the potential melting of the Greenland ice sheet could reduce the import of warm waters in the Golf stream to such an extent, that the European north-west coast could experience considerable decrease in its temperature.(In Czech, English summary only)